BIRTH WEIGHT AND RISK FACTORS FOR ATHEROSCLEROSIS -RETROSPECTIVE COHORT STUDY IN JAPANESE WORKERS. (April 2021) - Azegami, Tatsuhiko; Takeda, Ayano; Yokoyama, Hirokazu; Wainai, Yumiko; Hirose, Hiroshi; Makino, Shinji; Nishimura, Tomoyasu; Goto, Nobuko; Itoh, Hiroshi; Mori, Masaaki
Abstract : Objective: Low birth weight is associated with chronic health conditions later in life. B-type natriuretic peptide (BNP) is recently recognized as one of prognostic factors for cardiovascular events in general population. However, the association between the birth weight and BNP remains unclear. We aimed to examine the relation of birth weight with atherosclerotic risk factors including BNP among Japanese workers. Design and method: This study included 517 male and 592 female Japanese workers aged 40–70 years who attended an annual health checkup in 2018. The participants were divided into three groups according to their birth weight and evaluated the association between birth weight and risk factors for atherosclerosis including BNP, body mass index, blood pressure, creatinine, uric acid, triglyceride, HDL-cholesterol, LDL-cholesterol, glucose and HbA1c. Results: Trend test according to birth weight category showed that birth weight was inversely associated with HbA1c in men and with diastolic blood pressure in women, whereas it was not related with BNP levels in both men and women. Correlation coefficient test for birth weight data also revealed the correlation of birth weight with HbA1c in men (Pearson correlation coefficient -0.217, 95% CI [-0.350, -0.084]) and with diastolic blood pressure in women (-0.091, [-0.195, 0.000]), but not with log-transformed BNP level (-0.006, [-0.130, 0.142] for men, and -0.047 [-0.152, 0.057] for women). Multiple linear regression analysis indicated that birth weight was one of explanatory factors for HbA1c and regression model including birth weight, body mass index, ALT, creatine, hemoglobin, WBC, and platelet predicted HbA1c levels in men (R2 = 0.278). Conclusions: The present study showed no significant association between birth weight and BNP, whereas inverse associations of birth weight with HbA1c in men and with diastolic blood pressure in women were found. These data suggest that the birth weight may partially predict the future risk factors for atherosclerosis.